2012
DOI: 10.1242/jeb.066712
|View full text |Cite
|
Sign up to set email alerts
|

Differences in locomotor performance between individuals: importance of parvalbumin, calcium handling and metabolism

Abstract: SUMMARYLocomotor performance is linked to fitness and health of animals and is expected to be under strong selection. However, interindividual variation in locomotor performance is pronounced in many species. It was our aim to investigate the relative importance of energy metabolism and calcium handling in determining sprint and sustained locomotion in the zebrafish (Danio rerio). Sprint and sustained performance (U crit ) varied independently from each other. Using in vivo electroporation, we found that incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 76 publications
2
68
0
Order By: Relevance
“…Fast release of calcium from the sarcoplasmic reticulum increases force production but decreases fatigue resistance . Increased rates of resequestration of calcium into the sarcoplasmic reticulum by the sarco(endo)plasmic reticulum ATPase (SERCA) improves both sprint and sustained locomotion (Seebacher and Walter, 2012). ROS can interfere with calcium release dynamics from the sarcoplasmic reticulum and the calcium sensitivity of troponin (Cheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fast release of calcium from the sarcoplasmic reticulum increases force production but decreases fatigue resistance . Increased rates of resequestration of calcium into the sarcoplasmic reticulum by the sarco(endo)plasmic reticulum ATPase (SERCA) improves both sprint and sustained locomotion (Seebacher and Walter, 2012). ROS can interfere with calcium release dynamics from the sarcoplasmic reticulum and the calcium sensitivity of troponin (Cheng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In white muscle this increase in PV Ca 2+ affinity would disrupt the correct timing of muscle contraction by diverting Ca 2+ from binding to troponin C, which presumably could put fish at a disadvantage when trying to feed on swimming prey or when evading predators. Indeed, it has recently been shown that zebrafish swimming performance is correlated with PV content (Seebacher and Walter, 2012), indicating a role of PV in ecological fitness of teleost fish. For Antarctic fish PVs to function optimally we would expect to find evolutionary substitutions of amino acid residues compensating for the decreased ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Time to sexual maturity depends on growth rate and therefore on the capacity of energy assimilation and metabolism [25]. Foraging, competition and reproductive behaviour of animals are a function of locomotor performance and therefore of muscle physiology and metabolism [26,27]. Physiology acts as a filter between environmental changes, and ecology and biodiversity.…”
Section: Ecological Success Is Coupled To Environmental Conditions VImentioning
confidence: 99%